2021
DOI: 10.2478/jped-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

The gift of homeschooling: Adult homeschool graduates and their parents conceptualize homeschooling in North Carolina

Abstract: Although still a marginalized practice, homeschooling is on the rise internationally and across socio-economic groups. Moreover, the current Covid-19 pandemic has shifted additional attention to homeschooling. However, much of the available research is primarily concerned with the current day-to-day practice of homeschooling and little attention is paid to adult homeschool graduates. This exploratory study, based on qualitative interviews with mothers and adult children from 12 families, examines young adults’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…This research revealed the growing and diverse nature of homeschooling, emphasizing the importance of providing adequate support and resources for quality education. McCabe et al (2021) discussed the decisionmaking process behind homeschooling, highlighting the privilege and vulnerability of being a primary caregiver and educator in homeschooling families. They all suggest that homeschooling may benefit the state by reducing its role and expenses in providing care and education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This research revealed the growing and diverse nature of homeschooling, emphasizing the importance of providing adequate support and resources for quality education. McCabe et al (2021) discussed the decisionmaking process behind homeschooling, highlighting the privilege and vulnerability of being a primary caregiver and educator in homeschooling families. They all suggest that homeschooling may benefit the state by reducing its role and expenses in providing care and education.…”
Section: Discussionmentioning
confidence: 99%
“…According to McCabe et al (2021), a primary motivation for parents opting for homeschooling is their wish to offer religious or moral guidance and education to their children. Five of the 18 studies primarily discuss the positive effects of home education that appear in the learners' feelings and social interactions (Chase & Morrison, 2018;Cheng & Hamlin, 2023;Burke, 2022;Hartman & Huttunen, 2020;Davies, 2015).…”
Section: Why Do Parents Choose Homeschooling? How Do Homeschoolers Pe...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tal como pone de manifiesto la progresiva demanda de propuestas educativas como el homeschooling, el worldschooling, el unschooling o la ecopedagogía, (Morales Valero y Amber Montes, 2021). Frente a la visión reduccionista de que el homeschooling impide el correcto desarrollo social de los niños, distintas investigaciones han demostrado sus beneficios para la socialización (McCabe et al, 2021;Ray, 2021). Además, se ha demostrado la repercusión positiva de las pedagogías antiautoritarias en aspectos relacionados con la autoestima, la autorregulación emocional o la autoeficacia (Ponce-León, 2021;Perpiñà et al, 2022).…”
Section: Introductionunclassified